2018
DOI: 10.1364/oe.26.010716
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical optical response of nematic liquid crystal cells through electrically driven Fréedericksz transition: influence of the nematic layer thickness

Abstract: A dynamical optical characterization of planar nematic liquid-crystal cells electrically driven through the Fréedericksz transition is presented. Our method involves applying voltage steps with different starting voltage close to the Fréedericksz threshold. Measurements are performed on cells with various thickness, from a few microns up to 180µm, and highlight the transient molecular disorder occurring close to the Fréedericksz transition. We show that the transient disorder affects the molecular arrangement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…We have thus demonstrated the ability to exploit the birefringence of thick nematic cells (200µm), and to control them dynamically. In order to avoid diffusion and optical losses due to the Freédericksz transition in thick nematic layers, 68 we exploit the transient relaxation of the molecules. By applying a bias voltage onto the cell, LC molecules are brought out of equilibrium, then, the voltage is switched off, and LC molecules are dynamically driven back to their rest position.…”
Section: Salient Features Of the Hyperspectral Imaging Instrumentmentioning
confidence: 99%
“…We have thus demonstrated the ability to exploit the birefringence of thick nematic cells (200µm), and to control them dynamically. In order to avoid diffusion and optical losses due to the Freédericksz transition in thick nematic layers, 68 we exploit the transient relaxation of the molecules. By applying a bias voltage onto the cell, LC molecules are brought out of equilibrium, then, the voltage is switched off, and LC molecules are dynamically driven back to their rest position.…”
Section: Salient Features Of the Hyperspectral Imaging Instrumentmentioning
confidence: 99%
“…The mechanism relies on a tunable change of the LC optical index, either due to electrically-induced molecular orientation, or thermal-control of the nematic order [1,2]. Increasing the mixture birefringence together with the liquid crystal layer thickness (e.g., above 50 µm) enables enhancing the induced phase-shift and thus develop innovative applications [3,4]. Recently, electrically-addressed large cell gap nematics have attracted interests for terahertz phase shifters [5,6], high-resolution hyperspectral imaging [7][8][9][10], phase and group delay control of ultrashort pulses trains [11], tunable angular shearing in wedge-shaped cells [12] and terahertz vortex beam generators [13], just to cite a few.…”
Section: Introductionmentioning
confidence: 99%
“…SDI combined with Fourier analysis is a powerful metrology tool, already developed for optical coherent tomography [26], bulk group index measurement [27], phase response of metasurfaces [28] or ultrashort pulse characterization [29,30]. In previous publications, we have shown that common-path SDI performed with femtosecond pulses is suitable to achieve real-time tracking of the electro-optical changes in birefringence of nematics [3,11]. Here, we demonstrate that such a method, combined with broad spectral bandwidth (above 200 nm) and a low-coherence Michelson interferometer, takes advantage of the high chromatic dispersion of thick nematics.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in the majority of the reported cases, this range of the liquid crystal cell gap was on the order of tens of micrometers or less [5]. Recently, advanced [6] and emerging non-display applications of liquid crystals have resulted in a growing interest to develop and study thicker cells [7]. Thick liquid crystal cells are characterized by a higher phase shift according to Equation (1).…”
Section: Introductionmentioning
confidence: 99%